Magneto-optical trap reaction microscope for photoionization of cold strontium atoms - Ruan, Shushu; Yu, Xinglong; Shen, Zhenjie; Wang, Xincheng; Liu, Jie; Wu, Zhixian; Tan, Canzhu; Chen, Peng; Yan, Tian-Min; Ren, Xueguang; Weidemüller, Matthias; Zhu, Bing; et al. (Physical review, 2024)
We developed a magneto-optical trap reaction microscope (MOTREMI) for strontium atoms by combining multiparticle coincident detection with the laser cooling technique. The present compact injection system enables the production of cold Sr atoms in three modes of two-dimensional (2D) magneto-optical trap (MOT) beam, molasses, and three-dimensional (3D) MOT, providing adjustable densities and ratios of the ground state 5⁢𝑠2 (1𝑆0) and the excited states 5⁢𝑠⁢5⁢𝑝⁢1⁢𝑃1 and 3𝑃𝐽. The target profiles including temperature, density, and size of the 3D MOT as well as the 2D MOT beam cold atomic flux were characterized in detail. Using the present setup, we investigate the single photoionization of Sr atoms with molasses through few-photons absorption in 800 nm, where Sr+ and 𝑒− are detected in coincidence and most of the ionization channels are identified. The momentum resolution for coincident Sr+ and 𝑒− along time-of-flight direction are achieved up to 0.12 a.u. and 0.02 a.u., respectively. The spectra of photoelectron ionized from the ground state as well as several excited states show distinct structures manifesting prominent contributions from multiphoton absorption. Detecting complete vector momenta of electrons and recoil ions in coincidence paves a way for further investigation of two-electron correlation dynamics and multielectron effects with alkaline-earth atoms.
Gesehen am 27.09.2024